2010
DOI: 10.1097/jpn.0b013e3181cdb6e0
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors and Error in Perinatal Care

Abstract: Perinatal nurses work with intricate systems requiring frequent interface with complex technology. This interplay is strongly influenced by the work environment and systems operations. The interplay among worker, technology, and the environment increases the risk of medical error, adverse patient outcomes, and in some instances, healthcare team member injury. Human factors engineering is an applied science that provides the study of the interface between people and machines. Human factors engineers design oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Evidence supports nurses' perceptions that less time is spent with patients and more with the technologies like the electronic health record (Kossman & Scheidenhelm 2008). Yet, despite claims that technology enhances the delivery of safe, effective, efficient care, especially complex technology has shown to increase human error and potential for adverse outcomes (Mahlmeister 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports nurses' perceptions that less time is spent with patients and more with the technologies like the electronic health record (Kossman & Scheidenhelm 2008). Yet, despite claims that technology enhances the delivery of safe, effective, efficient care, especially complex technology has shown to increase human error and potential for adverse outcomes (Mahlmeister 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using a human factors approach, systems can be designed guided by our knowledge of human factors and, specifically, cognitive heuristics and biases in mind to improve usability and reduce the likelihood of human error related to alarm/ alert fatigue. 39 Phansalkar et al 40 published a review of the literature that identified numerous human factors that should be considered in the design of alarms/alerts, including, but not limited to, design (placement, visibility, color), alarm philosophy (logic), and cognitive factors (habituation, heuristics). Evidence-based recommendations to reduce alarm/alert fatigue include the implementation auditory alarms with distinct features, customization of alarms/alerts for individual patients or clinicians, and consideration of other strategies that reduce frequency and improve the sensitivity of alarms/alerts.…”
Section: Human Factors Engineeringmentioning
confidence: 99%
“…Using a human factors approach, systems can be designed guided by our knowledge of human factors and, specifically, cognitive heuristics and biases in mind to improve usability and reduce the likelihood of human error related to alarm/alert fatigue 39 . Phansalkar et al 40 published a review of the literature that identified numerous human factors that should be considered in the design of alarms/alerts, including, but not limited to, design (placement, visibility, color), alarm philosophy (logic), and cognitive factors (habituation, heuristics).…”
Section: Human Cognition and Decision Makingmentioning
confidence: 99%